Impression and levels of interaction among employees a case study on Philguard Security Services, Inc. - Abellanosa, Conrad Dominic
To determine impression and level of interaction of the employees of Philguard Security Services, Inc. using the systems theory. A rating scale was administered to thirty-five respondents comprising fourteen (140 employees working in the headquarters and twenty-four (24) security guards deployed in three (3) specific areas namely PhilAm Insurance Company, JFM Corporate Center, and Growth with Equity in Mindanao (GEM) Program. Some of the items were formulated in a manner that they will reflect the basic functions of the organization as a system and the possible interactions that exist in the organization. The scale for the impression part consisted of six(6) options corresponding to 1 as poor, 2 as fair, 3 as satisfactory, 4 as good, 5 as very good and 6 as excellent. The scale for the level of interaction part consisted of six(6) options corresponding to 1 as none, 2 as very weak, 3 as weak, 4 as moderate, 5 as strong and 6 as very strong. The first three of the options were considered to be negatively inclined while the bottom three were positively inclined. A dummy table was used to determine the frequency and percentage of the impression and level of interaction options alone. Tables were also used to analyze the frequency and percentage of all items considering the number of employees who answered the rating scale. The modes were determined to answer the statement of the problem. Results of the study showed that generally, Philguard as a system is working positively when taken into consideration are the equivalent percentages. However, the frequencies hold a heavier role since it is the evidence as to how many respondents chose a certain option. Good and very good for positive side and fair and satisfactory for the negative were the prominent options. They differ by 3 points at most. Thus, the organization has to evaluate and know the needs of the employees to attain a very positive impression. However, the organization needs to strengthens its efforts concerning it's judgment to the employees and the promotion and advancement opportunities. The level of interaction as well have little differences if taken into account are the frequencies. Efforts of the organization for its relationship to employees have to be intensified especially in considering their hands in decisions that affect their job. Results also clearly shows that employees can report, complain, and disagree with top management but the final decisions still are in the hands of top management. This, however, does not reinforce what the employees disclosed that they have a strong relationship with other employer.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication